1992
DOI: 10.1099/0022-1317-73-1-149
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage profiles of tobacco etch virus (TEV)-derived substrates mediated by precursor and processed forms of the TEV NIa proteinase

Abstract: Nucleotide sequences coding for proteins containing the tobacco etch virus (TEV) NIa proteinase were generated by polymerase chain reaction amplification and/or site-directed mutagenesis. These coding regions contained sequences for the proteinase alone or as part of higher Mr precursors. Following transcription and translation of these sequences in a cell-free system, the various polyproteins, all containing an active small nuclear inclusion protein (NIa) proteinase, were used to process a TEV substrate serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Recent in vitro studies with a variety of TEV polyproteins containing the NIa protease suggested that cleavage of the genomederived polyprotein is mainly directed by the 49K form of the protease, although the TEV 50K-71K protein junction (site B in Fig. 2) was differentially processed by several of the protease forms (Parks et al, 1992). However, as the authors emphasized, it is unknown to what extent these cell-free studies might reflect the actual situation in the infected cells.…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 89%
See 1 more Smart Citation
“…Recent in vitro studies with a variety of TEV polyproteins containing the NIa protease suggested that cleavage of the genomederived polyprotein is mainly directed by the 49K form of the protease, although the TEV 50K-71K protein junction (site B in Fig. 2) was differentially processed by several of the protease forms (Parks et al, 1992). However, as the authors emphasized, it is unknown to what extent these cell-free studies might reflect the actual situation in the infected cells.…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 89%
“…Recently, partial cleavage at PPV site A has been shown to occur in vitro (J. A. Garcia & J. L. Riechmann, unpublished results), although cleavage at the TEV site has not been detected (Parks et al, 1992), partial processing at this place presumably happens in vivo: TVMV proteins of 37K and 42K (probably P3 and P3 + 6K1) have been detected in infected plants by using antibodies raised against a bacterially expressed TVMV 42K protein originating from the P3+6K1 cistron . Sequence comparison studies of the two products that cleavage at this site would generate, P3 and 6K1, also favour the hypothesis of its existence (Lain et al, 1989a;.…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 99%
“…Certain evidence indicates that p6K1 is released from the polyprotein of PPV Riechmann et al, 1992) or TVMV (Rodriguez-Cerezo & Shaw, 1991), although this has not been observed for TEV (Parks et aL, 1992); the controversy lies in whether the P3-p6K1 site is cleaved. The region of the TuMV polyprotein containing the last 52 amino acids of P3, all of p6K1 and the first 53 amino acids of CI was aligned with that of five potyviruses (PPV, TEV, PVY, TVMV and PSbMV) (Fig.…”
Section: Proteolytic Processing Of the Polyproteinmentioning
confidence: 99%
“…Therefore, three different gene products would originate from this region of the potyvirus polyprotein: P3, 6K1 and P3 +6K a. However, in vitro processing at tobacco etch virus (TEV) site A has also been assayed and, in this case, no cleavage was observed (Parks et al, 1992). The presence of the presumed 6K t peptide in infected plants has not yet been observed for any potyvirus.…”
mentioning
confidence: 99%